The Analysis of Determinants of Developing Village Index in Indonesia - Prasetyo, Ahmad Danu; Sonny, Evita (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. Indonesia has been suffering from economic and social disparity. The most common gap occurs between rural and urban communities. This level of inequality also occurs within the villages themselves. Therefore, to support village development, The Ministry of Village, Development of Disadvantaged Regions, and Transmigration of Indonesia has developed Developing Village Index (Indeks Desa Membangun) to provide information and village progress status. This paper reviews the relation of the Developing Village Index with local factors. The author applies several local variables of 434 municipalities/districts in all over Indonesia using data of 2017. By using Multiple Linear Regression as the methodology, the author found a positive and significant relationship between the Human Development Index (X1) and Population Size (X3) toward the Developing Village Index (Y). Besides, the author also found a negative and significant relationship between Area Size (X2) and The Regional Level of Surplus and Deficit (X5) toward the Developing Village Index (Y). At the same time, some variables do not have a significant effect on Developing Village Index such as Local Government Capital Expenditure (X4) and Local Grant (X6).Keywords: Developing village index, human development index, local government capital expenditure, the regional level of surplus and deficit, local grant.